Pendampingan Ekonomi Masyarakat Difabel Kabupaten Jepara Pasca Pandemi Covid 19 - Murniati, Murniati; Arianto, Dwi Agung Nugroho; Rosdiana, Aliva; Andika, Husni (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The Economic Downturn in general has an impact on vulnerable communities. One of those affected by the pandemic storm is the disabled in Jepara Regency. PPDI (Indonesian Association of Persons with Disabilities) Jepara Regency is one of eleven disabled communities in Jepara that focuses on the microeconomic sector. The method used in this service is the ABCD (Asset Bassed Community Development) method. The purpose of this service is to provide assistance and training in HR management, business management and entrepreneurship training, independent business assistance and assist government and private banks in accessing capital and modifying the tools needed to support their business, providing assistance and training on online sales promotion and marketing management both direct and online sales. The results of this service are that partners can carry out their business by applying management knowledge, partners with disabilities have confidence in carrying out their business and partners can carry out their business by promoting their business through online and offline mechanisms and there is the opportunity to partner with a private bank, namely BMT Arta Abadi Jepara and get access to productive monitoring from Baznas Jepara Regency